Project management using Microsoft® Project 2013 : a training and reference guide for project managers using standard, professional, server, web application and project online - Cicala, Gus (Project Assistants, Inc. DelawareUS, 2013)
Serves as a comprehensive guide to running a project from initiation to closeout with guides to faciliate using Microsoft Project.